Light Weight Codec (LWC) an H.264 AVC influenced and macroblock-schemed codec for live streaming - Ajero, Eduardo Jose (2007)
Video conferences require video quality to be kept within a set range. It must be sensitive enough to clearly display even small details which may prove crucial for some types of discussions like online lectures. Because of limitations of current networks in handling large streams of data, codecs are made to compress these streams that are to be sent over the network. Two of the current standards widely used for videoconferences are H.263 and H.264 AVC. Since both of these codecs are comprehensive and are designed for a wide range of applications, this research results to an implementation of a codec that is influenced by the H.26x standards. Light Weight Codec (LWC) is a codec which has encoding modules patterned over H.26x features. An example is H.264's In-Loop Deblocking feature and LWC's Macroblock Degradation counter. It also introduces the option of being a macroblock-schemed codec compared to the usual frameschemed codecs. The codec achieves video compression by reusing macroblocks instead of making use of Intra-frames as done by H.263 and H.264 while still making use of standard encoding procedures like transforms and quantization. LWC is be able to encode incoming video stream in approximately a quarter of a second while performing at a rate of 10 to 20 frames per second, at an average of 150kbps.